A method for preparing an adhesive tissue engineering scaffold material based on suspension printing technology

The adsorable tissue engineering scaffold material prepared through suspension printing technology solves the side effects and structural design limitations of traditional scaffold material fixation methods, realizes the structural design and efficient adhesion of scaffold material, is suitable for personalized medical needs, and is displayed in the body Good biocompatibility and adhesion ability.

CN116175956BActive Publication Date: 2024-12-24PEKING UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310015230.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2024-12-24
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

Traditional tissue engineering scaffold materials require suture or bio-glue fixation, which may cause secondary damage or side effects. Stent materials with autonomous sticking function cannot be structurally designed, and the application form is amorphous hydrogel.

Method used

Using adsorable tissue engineering scaffold material prepared based on suspension printing technology, the scaffold structure is designed through 3D printing technology, including vascular structure and cell arrangement, and the suspension printing technology is used to print and cure in the supporting material, and then surface modification is carried out to improve the stickiness. Attached ability.

Benefits of technology

The structural design and efficient adhesion of scaffold materials are achieved, which improves cell survival and proliferation ability, is suitable for personalized medical needs, and shows sufficient tissue adhesion and biocompatibility in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116175956B_ABST
    Figure CN116175956B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing an adhesive tissue engineering scaffold material based on suspension printing technology. The method comprises the following steps: 1) structural design of the tissue engineering scaffold material to be prepared; 2) 3D printing and curing the pre-liquid (printing ink) of the tissue engineering scaffold material according to the designed pattern to obtain the cured tissue engineering scaffold material; 3) surface modification of the cured tissue engineering scaffold material. The material of the present invention can have the advantages of 3D printing and autonomous adhesion. Experiments have shown that it has the ability to adhere to tissues in vivo, suitable swelling properties, mechanical properties, porosity and biocompatibility, and high printing accuracy. It is an autonomously adhesive scaffold material that can be used for structural design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medicine, and specifically relates to a method for preparing an adhesive tissue engineering scaffold material based on suspension printing technology. The technology can be used to repair damaged tissues or organs. The tissue engineering scaffold is a biological material that fills the damaged tissue site and replaces the extracellular matrix of the damaged tissue to provide space and nutrients for cell growth and proliferation in the damaged site. After the cells grow and proliferate to form mature tissues, they will gradually degrade. Background Art

[0002] Commonly used tissue engineering scaffold fixation methods have defects: tissue engineering scaffold materials are often connected to tissues and fixed on them by suture or biological glue. Sutures often cause secondary damage to damaged tissues, and commonly used biological glues often have certain side effects. For example, cyanoacrylate has inappropriate strength and certain toxicity, and fibrin glue may have infection risks. In addition, biological glue may form a barrier between the scaffold and the tissue, affecting the communication between cells in the scaffold and the tissue, and affecting the fusion of the scaffold and the tissue. Tissue engineering scaffold materials with self-adhesive function can directly contact the damaged tissue and be autonomously fixed to the surface of the damaged tissue, thereby avoiding the side effects of using traditional suture or biological glue methods.

[0003] Limitations of other tissue engineering scaffolds with autonomous tissue adhesion function: In recent years, there have been some cases of tissue engineering scaffolds with autonomous tissue adhesion function. The application form is generally to add hydrogel precursor droplets to the tissue surface, directly solidify on the tissue surface to form a hydrogel scaffold material that can be attached to the tissue. The limitation of this method is that the hydrogel directly added to the tissue surface and solidified is amorphous and cannot be structurally designed.

[0004] In the field of tissue engineering, past studies have shown that there are many advantages to structural design of tissue engineering scaffolds. For example, tissue engineering scaffolds have a certain thickness, and the cells contained in them need to transport nutrients and metabolic waste. Designing a vascular structure inside the scaffold can facilitate the transportation of nutrients and metabolic waste by cells, and improve cell survival and proliferation. In addition, tissues are often composed of a variety of cells, and the cells are arranged. When designing a scaffold, adding different types of cells in the tissue and arranging the cells can help the scaffold material better replace the damaged tissue. Furthermore, the area and degree of damage to different individual tissues are different. The preparation of scaffolds that meet the individual damage area and morphology is in line with the concept of "personalized medicine" and can provide patients with personalized treatment that suits their wounds. 3D printed scaffolds can meet the above three requirements and can break through the limitations of traditional tissue engineering scaffolds with autonomous tissue adhesion functions. Summary of the invention

[0005] The technical problem to be solved by the present invention is that traditional tissue engineering scaffold materials often need to be fixed by means of suturing or biological glue, which may cause secondary damage or side effects, and the tissue engineering scaffold materials with self-adhesive properties published in previous literature often cannot be structurally designed. Their application form is generally to drop the hydrogel precursor on the tissue surface and directly solidify it on the tissue surface to form a hydrogel scaffold material that can be attached to the tissue. The limitation of this method is that the hydrogel directly dropped on the tissue surface and solidified is amorphous and cannot be structurally designed.

[0006] The object of the present invention is to provide an adhesive tissue engineering scaffold material based on suspension printing technology and a preparation method thereof. The tissue engineering scaffold material prepared by 3D printing can utilize 3D printing technology to design the structure of the scaffold material. For example, inside the scaffold material, the addition of a vascular structure helps to improve the exchange of nutrients and metabolites, thereby improving the probability of cell survival and the efficiency of proliferation and differentiation. In addition, designing a personalized scaffold material that conforms to the wound morphology according to the individual's injury condition is conducive to better fitting the scaffold to the wound and realizing personalized medicine. Furthermore, there are often multiple cells arranged in a regular pattern in biological tissues. Tissue engineering scaffold materials, as a temporary replacement for damaged defective tissues, can better realize their function of temporary tissue replacement if they can imitate the original tissue structure to distribute and arrange different types of cells in a regular manner inside the scaffold.

[0007] The method for preparing an adhesive tissue engineering scaffold material based on suspension printing technology provided by the present invention comprises the following steps:

[0008] 1) Structural design of the tissue engineering scaffold material to be prepared;

[0009] 2) 3D printing and curing the precursor liquid (printing ink) of the tissue engineering scaffold material according to the designed pattern to obtain the cured tissue engineering scaffold material;

[0010] 3) The solidified tissue engineering scaffold material is subjected to surface modification to obtain the obtained material.

[0011] In step 1) of the above method, the structural design includes the design of the vascular structure, the arrangement and shape of the cells, etc.;

[0012] The specific operation is: use CAD software to design the structure of the tissue engineering scaffold material to be prepared, and then convert it into a Gcode file that can be recognized by the printing machine.

[0013] In step 2) of the above method, the 3D printing adopts biological 3D printing technology.

[0014] In 3D printing technology, a FRESH printing method may be specifically adopted.

[0015] Suspension printing is a form of extrusion printing. Its principle is to extrude the printing ink into the support material in layers from bottom to top according to the pre-designed pattern, and then solidify it in the support material, dissolve the support material and take out the solidified support material. Suspension printing has higher printing accuracy than other extrusion printing methods, and can realize the printing of inks that do not have self-supporting ability.

[0016] Using the suspension printing method, the specific operation of step 2) is: printing the printing ink in the support material through the bioprinting device, curing, removing the support material, and obtaining the cured tissue engineering scaffold material.

[0017] The support material is formed by a Carbopol microsphere solution. The Carbopol microspheres are mixed with deionized water at a ratio of 0.5wt%-1.0wt% (specifically 0.8wt%). After 20-24 hours, the pH value of the mixed solution is adjusted to neutral to obtain a viscous support material that can support printing ink.

[0018] Furthermore, 0.5wt%-1.0wt% (specifically 0.75wt%) of kinipin and 0.2-0.25mM (specifically 0.2mM) of H2O2 are added to the support material as initiators for curing the printing ink.

[0019] The printing ink comprises the following components: gelatin, methacryloyl gelatin (GelMA) and tyramine grafted methacryloyl hyaluronic acid (HAMA-Tyr), and also contains a photoinitiator and an initiator for initiating HAMA-Tyr cross-linking.

[0020] The photoinitiator may specifically be phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP);

[0021] The initiator for initiating HAMA-Tyr cross-linking can specifically be horseradish catalase.

[0022] In an embodiment of the present invention, 0.25% HAMA-tyr, 5% GelMA, and 5% gelatin are dissolved in deionized water, and 0.25% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is added as a photoinitiator and 10U / ml catalase is used as a cross-linking initiator to obtain printing ink.

[0023] In step 3) of the above method, the surface modification is divided into two steps. The first step is to coat the surface of the scaffold material with dopamine; the second step is to dry the scaffold material after coating.

[0024] Wherein, the surface dopamine coating operation is to immerse the stent material in a dopamine aqueous solution, the concentration of the dopamine aqueous solution may be 0.01 g / ml, and the immersion time may be 8-12 minutes, specifically 10 minutes;

[0025] Remove water droplets from the surface of the support material before immersion;

[0026] The drying step is performed at 37° C. for 10 min.

[0027] The adhesive tissue engineering scaffold material prepared by the above method also belongs to the protection scope of the present invention.

[0028] When in use, the obtained adhesive tissue engineering scaffold material (without gel) is attached to the damaged organ or tissue and exposed to blue light to complete the adhesion of the tissue engineering scaffold material to the organ or tissue.

[0029] We characterized its tissue adhesion ability in vitro and in vivo. Adhesion tests were performed in a mouse myocardial infarction model to demonstrate that the material has sufficient tissue adhesion. In addition, the mechanical strength, swelling properties, porosity and biocompatibility of the scaffold material were tested.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] It can be used to prepare tissue engineering scaffold materials with sufficient tissue adhesion ability and can design the internal structure of the scaffold material for repairing damaged organs and tissues.

[0032] To demonstrate its beneficial effects, we tested the adhesion of the scaffold material in vivo and in vitro.

[0033] In the attached Figure 6 In C, the highest group (group D) has an adhesion strength of 5.45±2.16 kPa, which is a significant improvement compared to the 1.05±0.06 kPa before modification. Figure 6In D, it can be observed that the scaffold material adhered to the collagen membrane can still adhere to the collagen membrane after being immersed in water for 1 hour. This method can qualitatively prove the adhesion performance of the scaffold in the water environment. The adhesion in the in vitro water environment has a reference value for the adhesion ability in vivo. In Figures 6E and F of Appendix, it can be seen from the results of the in vivo adhesion test conducted in the mouse myocardial infarction model that the scaffold is still adhered to the surface of the mouse heart after one month, reflecting the adhesion ability of the scaffold material on living tissue.

[0034] In addition, to prove that the scaffold material can support the growth and reproduction of cells, we conducted tests related to cytotoxicity, swelling properties and scaffold porosity. At the same time, we conducted mechanical tests to observe the mechanical strength of the scaffold material.

[0035] In Figure 4F of Appendix, we can observe that the swelling ratio of the stent material is less than 10%, which has good swelling performance and can avoid problems such as deformation of the stent structure and squeezing of tissues caused by excessive swelling. Figure 5 In Figure B, it can be seen that the absorbance of cck8 of the scaffold material on day 3 is higher than that of the control group. In Figure 5A of Appendix, the live / dead results show that the number of live cells is far greater than the number of dead cells, and the number of cells on day 3 is far greater than the number of cells on day 1, indicating that the scaffold material has the ability to support cell growth and proliferation, indicating that it has good biocompatibility. Figure 4 In E, the mechanical strength of the scaffold material is about 20 kPa, which is consistent with the strength range of myocardial tissue, artery, smooth muscle tissue, breast tissue, liver tissue and other tissues, indicating that the scaffold material can be used to repair such tissues. Figure 3 Among them, the pore sizes of group A and group D (the most viscous groups) are mainly distributed between 30-60 μm, with appropriate porosity.

[0036] Finally, we tested the printing accuracy of 3D printing. The characterization of printing accuracy can be divided into two aspects: one is the characterization of the ink printing ability and accuracy, and the other is the characterization of the overall accuracy of the printed 3D structure. Figure 4 In A, the lines printed by the ink are continuous, and the ratio of the line diameter to the needle diameter is 99.6±9.0%. Figure 4 In B, the ratio of the area of ​​the printed letter "P" to the original area is 100.4±9.4%, indicating a high printing accuracy.

[0037] In summary, we have designed a material that combines the advantages of 3D printing and autonomous adhesion. Our experiments have proven that it has the ability to adhere to tissues in vivo, suitable swelling properties, mechanical properties, porosity and biocompatibility, and high printing accuracy. It is a self-adhesive scaffold material that can be used for structural design.

[0038] The scaffold material we designed was pasted on the hearts of living mice after myocardial infarction, demonstrating that it has sufficient tissue adhesion ability and biocompatibility and can adhere to the surface of the heart of living mice for up to four weeks. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a preparation process of an adhesive tissue engineering scaffold material. The printing ink is loaded into a printing device, and printing is performed in a supporting material according to a model. After printing is completed, the ink is placed in the supporting material overnight to achieve cross-linking. After the ink is solidified, the scaffold material is released from the supporting material with a PBS solution. Thereafter, the scaffold material is placed in a dopamine hydrochloride solution to achieve surface modification of dopamine, and the scaffold material is dried at 37° C. for 10 minutes to remove surface moisture. Thereafter, the scaffold material can be combined with the tissue surface and exposed to blue light, and the scaffold material can be combined with the tissue surface through the chelation produced by dopamine and the autonomous adhesive ability produced by the reaction of the free radicals formed by the double bonds of the MA group with the tissue surface groups.

[0040] Figure 2 Synthesis of polymer materials in bio-ink. A: Synthesis of HAMA-tyr. a: Protons on the methyl group on hyaluronic acid, b: Protons on the double bond of grafted acrylic acid, c: Protons on the grafted benzene ring. B: Synthesis of GelMA. d: Protons on the amino group on gelatin, e: Protons on the double bond of grafted acrylic acid. C: Principle of cross-linking inside the scaffold. f shows the cross-linking between tyramine triggered by hydrogen peroxide and catalase, g shows the cross-linking of GelMA triggered by blue light, and h shows the cross-linking of gelatin molecules triggered by genipin.

[0041] Figure 3 The pore structure of the scaffold material. A: The cross-sectional pores, surface pores and pore structure of the transition area from the surface to the cross-sectional area of ​​group A. B: The statistical histogram of the surface and cross-sectional pore sizes of group A. C: The cross-sectional pores, surface pores and pore structure of the transition area from the surface to the cross-sectional area of ​​group D. D: The statistical histogram of the surface and cross-sectional pore sizes of group D. (n=100). The scale bars in A and C represent 100 μm.

[0042] Figure 4Characterization of printing accuracy and physical properties of the scaffold. A: Continuous lines formed by printing ink on a plane. B: Letter P printed by the FRESH method. C: Printing accuracy obtained by measurement from Figures A and B compared with the template. D: Displacement-load curve of the scaffold material. E: Young's modulus of the scaffold material. F: Evaluation of the swelling rate of the scaffold material. (n=4). The scale of Figure A represents 1 mm, and the scale of Figure B represents 1 cm.

[0043] Figure 5 Characterization of cell compatibility. A: Cell live and dead in group A and group D on day 1 and day 3. B: Relative absorbance of cck8. The experimental group is the absorbance generated by the cells interacting with cck8 after growth in the extracts of different groups, and the control group is the absorbance generated by the cells interacting with cck8 after growth in cell culture medium. The relative absorbance is the ratio of the absorbance of the experimental group to that of the control group. (n=4) The scale bar in Figure A represents 200μm.

[0044] Figure 6 In vivo and in vitro testing of scaffold material adhesion. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0046] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0047] Example

[0048] Drawing of bioprinting model: The bioprinting model is drawn by CAD software. Note: The present invention is a design of a scheme and platform. People who refer to or use the invention can design different models according to their own needs in practical applications.

[0049] Convert the model into printable code: Convert the CAD model into G code or NC format code using software, such as Repetier. This code can be recognized by the printing device, so that it can be printed according to the coordinates.

[0050] Preparation of printing ink: The ink is composed of gelatin, gelatin methacryloyl (GelMA) and tyramine grafted hyaluronic acid methacrylate (HAMA-Tyr). Gelatin can be purchased through Sigma Reagent Company.

[0051] Figure 2 For the synthesis of polymer materials in bio-ink.

[0052] The synthesis of GelMA is as follows: 20g of gelatin is dissolved in 200ml of deionized water, the solution is heated to 50°C, and the pH value of the solution is adjusted to between 8-11. 2g of methacrylic anhydride is added to the solution in 10 times, and the pH value of the solution is adjusted after each addition so that it is kept between 8-11, and the temperature is kept at 50°C throughout the process. After all the methacrylic anhydride is added, react at 50°C and pH between 8-11 for 1h, then adjust the pH value of the solution to neutral, dilute the solution to 600ml, filter the impurities in the solution through a syringe filter, and dialyze at 30°C for 72h, then freeze-dry it in a freeze dryer to obtain GelMA solid.

[0053] The synthesis of HAMA-Tyr is as follows: 1g hyaluronic acid (HA) is dissolved in 100ml deionized water, the solution is placed in an ice bath, methacrylic anhydride (MA) is added dropwise and the pH value of the solution is maintained between 8-11, and a total of methacrylic anhydride is added at a molar ratio of 5:1 (MA:HA=5:1) to the hyaluronic acid monomer. After stirring the reaction for 3h, the solution is placed at 4°C for 24h, the solution is poured into 3 times the volume of ice ethanol, the white precipitate is collected, the white precipitate is placed in a dialysis bag for 3 days and freeze-dried to obtain a methacrylic acid grafted hyaluronic acid solid (HAMA). Dissolve 1g HAMA in 100ml water, adjust the pH to neutral, add tyramine (tyr:HAMA=1.5:1) at a molar ratio of 1.5:1 to HAMA monomer, and add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) at a molar ratio of 1.5:1 to HAMA monomer as initiators (EDC / NHS:HAMA=1.5:1), and react with stirring at room temperature. After 10h, stop the reaction, place the solution in a dialysis bag for 3 days, and freeze-dry to obtain HAMA-Tyr.

[0054] 0.25% HAMA-tyr, 5% GelMA, and 5% gelatin were dissolved in deionized water, and 0.25% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was further added as a photoinitiator and 10 U / ml catalase was used as a cross-linking initiator to obtain printing ink.

[0055] In the above synthesis, hyaluronic acid, gelatin, tyramine, EDC, NHS, LAP, and catalase can be purchased from Sigma Reagents.

[0056] Preparation of support material: Carbopol was added to deionized water to obtain a 0.8% solution. After stirring for 24 hours, 0.75% wt genipin and 0.2 mM H2O2 were added to the solution. After stirring for 1 hour, the pH of the solution was adjusted to neutral to form a viscous solid as a support material for carrying uncured printing ink.

[0057] according to Figure 1 The flowchart shown is for the preparation of adhesive tissue engineering scaffold materials.

[0058] The process of bioprinting: the ink is printed in the support material according to the pre-designed model and the code generated according to the model. After printing, the support material containing the ink is left to stand. The catalase in the ink can trigger the decomposition of hydrogen peroxide, generating free radicals to trigger the cross-linking of HAMA-tyr. At the same time, the genipin in the ink can trigger the cross-linking of gelatin, so that the ink is cross-linked and solidified in the support material to form a solid support material with a fixed shape. After solidification, PBS solution is added to the support material to dissolve the support material and remove the support.

[0059] Surface modification of the scaffold material: The scaffold material was immersed in a 0.01% dopamine aqueous solution for 10 minutes, a layer of dopamine was coated on the surface of the scaffold, and the scaffold material was placed at 37° C. for 10 minutes for drying to remove moisture on the surface of the scaffold and improve the biological viscosity of the scaffold.

[0060] Figure 3 The pore structure of the scaffold material.

[0061] The preparation process of each group in the accompanying drawings is as follows:

[0062] Table 1: Preparation methods of each group

[0063]

[0064] Application of scaffold materials: Attach the surface-modified scaffold material to the tissue surface, and use a blue light source to trigger the reaction of the MA groups in the scaffold materials HAMA-tyr and GeLMA, so that the MA groups generate free radicals. The MA groups can react with each other, and the free radicals generated by MA can also react with the amino or hydroxyl groups on the tissue surface, thereby improving the bonding between the scaffold and the tissue and improving the viscosity of the scaffold material.

[0065] To prove that the scaffold material can support the growth and reproduction of cells, we conducted tests related to cytotoxicity, swelling properties and scaffold porosity. At the same time, we conducted mechanical tests to observe the mechanical strength of the scaffold material.

[0066] Figure 4 To characterize the printing accuracy and physical properties of the scaffold.

[0067] Figure 5 Characterization of cell compatibility.

[0068] Figure 6 In vivo and in vitro testing of the adhesion of the stent material. A: Device for measuring adhesion in vitro. Two aluminum alloy T-plates are clamped on the mechanical tester. The collagen membrane is glued to one of the T-plates with glue, and the stent material is glued to the collagen membrane. The other side of the stent material is glued to the T-plate with glue. During the measurement, the mechanical tester will pull the T-plates apart from the upper and lower ends until the adhesion between the stent material and the collagen membrane is broken. B: Schematic diagram of the in vitro adhesion measurement device. C: Test results of in vitro adhesion. (n=4). D: Qualitative test of the adhesion ability of the stent material in vitro under water. The stent material adheres to the collagen membrane. The collagen membrane and the stent material are immersed in water together. After 1 hour, the stent material is still adhered to the surface of the collagen membrane. E: The result of adhering the stent material to the mouse heart in the mouse myocardial infarction model for one month. The stent material is still adhered to the surface of the heart. F: Masson staining of the mouse heart. The staining is of a mouse heart that did not undergo myocardial infarction surgery, a mouse heart that underwent myocardial infarction surgery and had scaffold material attached, and a mouse heart that underwent myocardial infarction surgery and did not have scaffold material attached. The scaffold material is marked with a black arrow.

[0069] Figure 6 In C, the highest group (group D) has an adhesion strength of 5.45±2.16 kPa, which is a significant improvement compared to the 1.05±0.06 kPa before modification. Figure 6In D, it can be observed that the scaffold material adhered to the collagen membrane can still adhere to the collagen membrane after being immersed in water for 1 hour. This method can qualitatively prove the adhesion performance of the scaffold in the water environment. The adhesion in the in vitro water environment has a reference value for the adhesion ability in vivo. In Figures 6E and F of Appendix, it can be seen from the results of the in vivo adhesion test conducted in the mouse myocardial infarction model that the scaffold is still adhered to the surface of the mouse heart after one month, reflecting the adhesion ability of the scaffold material on living tissue.

[0070] In Figure 4F of Appendix, we can observe that the swelling ratio of the stent material is less than 10%, which has good swelling performance and can avoid problems such as deformation of the stent structure and squeezing of tissues caused by excessive swelling. Figure 5 In B, it can be seen that the cck8 absorbance of the scaffold material on day 3 is higher than that of the control group. In Figure 5A of Appendix, the live / dead results show that the number of live cells is far greater than the number of dead cells, and the number of cells on day 3 is far greater than the number of cells on day 1, indicating the scaffold material's ability to support cell growth and proliferation, indicating that it has good biocompatibility.

[0071] In the attached Figure 4 In E, the mechanical strength of the scaffold material is about 20 kPa, which is consistent with the strength range of tissues such as myocardial tissue, artery, smooth muscle tissue, breast tissue, and liver tissue, indicating that the scaffold material can be used to repair such tissues.

[0072] In the attached Figure 3 Among them, the pore sizes of group A and group D (the most viscous groups) are mainly distributed between 30-60 μm, with appropriate porosity.

[0073] Finally, we tested the printing accuracy of 3D printing. The characterization of printing accuracy can be divided into two aspects: one is the characterization of the ink printing ability and accuracy, and the other is the characterization of the overall accuracy of the printed 3D structure. Figure 4 In A, the lines printed by the ink are continuous, and the ratio of the line diameter to the needle diameter is 99.6±9.0%. Figure 4 In B, the ratio of the area of ​​the printed letter "P" to the original area is 100.4±9.4%, indicating a high printing accuracy.

[0074] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for preparing an adhesive tissue engineering scaffold material based on suspension printing technology, comprising the following steps: 1) Structural design of the tissue engineering scaffold material to be prepared; 2) 3D printing and curing the printing ink of the tissue engineering scaffold material according to the designed pattern to obtain the cured tissue engineering scaffold material; In step 2), the 3D printing adopts a suspension printing method, and the specific operation is: printing the printing ink in the support material through a bioprinting device, curing, removing the support material, and obtaining a solidified tissue engineering scaffold material; The printing ink comprises the following components: gelatin, methacrylated gelatin and tyramine-grafted methacrylated hyaluronic acid, and also contains a photoinitiator and an initiator for initiating cross-linking of the tyramine-grafted methacrylated hyaluronic acid; in, The photoinitiator was lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP); The initiator for initiating the cross-linking of tyramine-grafted methacrylylated hyaluronic acid is horseradish catalase; 3) Surface modification of the solidified tissue engineering scaffold material is performed to obtain; In step 3), the surface modification is divided into two steps. The first step is to coat the surface of the scaffold material with dopamine; the second step is to dry the scaffold material after coating.

2. The method according to claim 1, characterized in that: In step 1), the structural design includes the design of the vascular structure, the arrangement of cells and the design of the appearance; The specific operation is: use CAD software to design the structure of the tissue engineering scaffold material to be prepared, and then convert it into a Gcode file that can be recognized by the printing machine.

3. The method according to claim 1, characterized in that: The support material is formed from a Carbopol microsphere solution. The Carbopol microspheres are mixed with deionized water at a ratio of 0.5 wt%-1.0 wt%, and the pH value of the mixed solution is adjusted to neutral after 20-24 hours to obtain the support material.

4. The method according to claim 3, characterized in that: Add 0.5wt%-1.0wt% of kinipin and 0.2-0.25mM H2O2 to the support material as initiators for curing the printing ink.

5. The method according to claim 1, characterized in that: 0.25% HAMA-tyr, 5% GelMA, and 5% gelatin were dissolved in deionized water, and 0.25% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was added as a photoinitiator and 10 U / ml catalase was added as a cross-linking initiator to obtain a printing ink.

6. An adhesive tissue engineering scaffold material prepared by the method according to any one of claims 1 to 5.

7. The adhesive tissue engineering scaffold material according to claim 6, characterized in that: When in use, the adhesive tissue engineering scaffold material is attached to a damaged organ or tissue and exposed to blue light to complete the adhesion of the tissue engineering scaffold material to the organ or tissue.

Citation Information

Patent Citations

  • 3D printed Ti-PDA-BMP-2 bone defect repair tissue engineering scaffold and preparation method thereof

    CN108939156A

  • Printing material, bone tissue engineering scaffold loaded with stem cells and preparation method of bone tissue engineering scaffold

    CN109999226A

  • Multi-stage suspension printing method for constructing complex heterogeneous tissue / organ

    CN113290844A

  • High-comprehensive-performance photocuring biological 3D printing composite hydrogel as well as preparation method and application thereof

    CN113713179A

  • Additive Manufacturing of Channels

    US20200047399A1